Scleritis and anterior uveitis may herald the development of an epibulbar tumor in patients with extranodal Rosai-Dorfman disease: a case report - Yu-Kuei Lee; Sheau-Chiou Chao; Chaw-Ning Lee; Jia-Horung Hung (BMC Ophthalmology, 2019)
Abstract Background Rosai-Dorfman disease is a rare non–Langerhans cell histiocytosis. Ocular involvement is even rarer, mostly involving the orbit and eyelids, although marginal corneal ulcers, uveitis, and epibulbar masses have also been reported, and is characterized by multiple recurrences. However, the disease course and optimal treatment strategies remain undetermined, in light of the rarity of this disease. Case presentation We reported a 36-year-old male patient with the extranodal form of Rosai-Dorfman disease, presenting with scleritis and anterior uveitis in the left eye, who experienced subsequent development of an epibulbar tumor in the same eye. The patient was also complicated by a relapsing facial nodule on the right cheek. After the pathological diagnosis of Rosai-Dorfman disease was obtained, the patient underwent surgical excision of the epibulbar tumor and the facial nodule, accompanied by systemic immunosuppression therapy. At the last follow-up, the patient was asymptomatic without signs of recurrence. Conclusions This report highlights the progression of ocular manifestations of Rosai-Dorfman disease and emphasizes the importance of systemic therapy.